1997
DOI: 10.1080/15216549700203361
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ca2 transport activity associated with a non‐mitochondrial calcium pool in the rodent malaria parasite P. chabaudi

Abstract: SUMMARYNon-mitochondrial calcium deposits were investigated in the intraerythrocytic malaria parasite Plasmodium chabaudi at the trophozoite stage by means of arsenazo III in the presence of ATP and the mitochondfial poisons, antimycin and oligomycin . Addition of vanadate and 2,5-di-(t-butyl)-l,4-hydroquinone (BHQ), both known to interact with SERCA pump, induced calcium release by permeabilized parasites when the medium free calcium concentration was kept at 3.5 ~tM. The tumor promoter thapsigargin also caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…To investigate the source of the observed Ca 2+ oscillations, we depleted Ca 2+ stores before imaging by using thapsigargin (Tg), a specific inhibitor of sarco/endoplasmic reticulum Ca 2+ –ATPase, and concanamycin A (CMA), a specific inhibitor of vacuolar-type H + -ATPase. The effects of these inhibitors have been demonstrated in Plasmodium species [28][30]. We also confirmed the effectiveness of these compounds in depleting Ca 2+ by Ca 2+ imaging in early ring forms and early trophozoites using perfusion experiments (Fig.…”
Section: Resultssupporting
confidence: 80%
“…To investigate the source of the observed Ca 2+ oscillations, we depleted Ca 2+ stores before imaging by using thapsigargin (Tg), a specific inhibitor of sarco/endoplasmic reticulum Ca 2+ –ATPase, and concanamycin A (CMA), a specific inhibitor of vacuolar-type H + -ATPase. The effects of these inhibitors have been demonstrated in Plasmodium species [28][30]. We also confirmed the effectiveness of these compounds in depleting Ca 2+ by Ca 2+ imaging in early ring forms and early trophozoites using perfusion experiments (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The digestion of the Hb takes place at the food vacuole, and it has been suggested that this organelle is the acidic compartment where antimalarial drugs such as chloroquine are accumulated (Yayon et al, 1984) and prevents haemozoin polymerization (Goldberg and Slater, 1992). However, this compartment also accumulates Ca 2+ in human and rodent malaria parasites (Passos and Garcia, 1997; Garcia et al, 1998; Marchesini et al, 2000; Varotti et al, 2003; Rohrbach et al, 2005; Bagnaresi et al, 2009). Calcium handling mechanisms in these organisms have been extensively studied by several authors (Wasserman, 1990; Adovelande et al, 1993; Hotta et al, 2000; Beraldo et al, 2005; Sartorello et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are three Ca 2+ compartments in malaria parasite: endoplasmic reticulum (ER) (Passos & Garcia ), acidic compartment (Varotti et al . ) and mitochondrion (Gazarini & Garcia ).…”
Section: Resultsmentioning
confidence: 99%